Managerske napovedi in dejanski učinki pandemije covid-19 na slovenska podjetja - Bešter, Janez (Teorija in praksa, 2023)
Predicting the financial performance of companies is a challenging task even in normal business circumstances, with the uncertainties brought about by COVID-19 pandemic having further added to this challenge. In this article, we examine the responses of managers from 154 Slovenian companies to a survey taken in the spring of 2020 at the end of the first pandemic wave, and compare them to their actual financial performance for the years 2019, 2020 and 2021. Our findings show no significant links between the pre-pandemic financial performance and management survey predictions. Still, managers accurately predicted the pandemic’s impact on the financial performance of their companies in 2020 and 2021.
Keywords: companies; Covid-19; effects; finance; indicators; indikatorji; management; napovedi; Napovedovanje; pandemic; pandemija; podjetja; Poslovni uspeh; predictions; učinek